scale in tourism satisfaction - Al Salmi, Muatasim (Advances in Social Sciences Research Journal, 2019)
E-government construction requires technical development and implementation solutions from private sector in the country. Both sectors, tourism and government are facing obstacles and challenges generated by the advance and improvement in the use of ICTs by consumers and citizens. Ksenia et al. (2014) illustrated that there are 21 dimensions of tourist satisfaction toward aesthetic judgment and effects in behavioral intention to visit and revisit. This report presents the Uniqueness dimension’s overview from the 21 dimensions to be visited and discussed using a case study of GCC interviews in order to conduct conclusion and recommendations to the GCC nations.